Studying drug prescription pattern of dermatology OPD of an Indian tertiary care hospital- a prospective, observational, cross-sectional study - Baig, Mirza Shiraz; Kulkarni, Vishal; Medhekar, Sudhir (International Journal of Research in Medical Sciences, 2023)
Background: Studying prescription patterns helps prescribers to provide rational and cost-effective medical care. Drugs prescribed for skin disorders by a specialist differ in terms of numbers and the selection of drug class, necessitating periodic prescription audits and drug utilization studies. Methods: This prospective, cross-sectional, observational study was conducted at the dermatology department OPD of Government Medical College, Aurangabad (Maharashtra, India) from January 2021 to May 2021. Digital records of prescription were collected from the hospital management information system (HMIS). Results: N=5338 prescriptions were analysed, 40.89% of patients were from the 21-35 years age group. Polytherapy was 62.96% and monotherapy 36.99%. Drugs prescribed by generic names were 18% and brand names were 82%. Topical drugs constituted 71.67% followed by systemic drugs 28.32% of total prescriptions and the average injectables prescribed per encounter was 0.33%. Antifungals were most prescribed followed by steroids. The average number of drugs prescribed was 1.85 per encounter and the percentage of antibiotic prescriptions was 17.70%. Conclusions: The current study showed that WHO DUS indicators were followed. The results reflect rational prescription of drugs within the available resources.